Joint optimization algorithm for continuous/discrete phase beamforming in active Reconfigurable Intelligent Surfaces - Zhang, Qianqian; Han, Zhengjiang; Cao, Folong; Wang, Erfu (International journal of electronics and communications, 2025)
In this paper, a unified optimization framework for both continuous and discrete phase configurations of active Reconfigurable Intelligent Surfaces (RIS) phases method is proposed. An adaptive temperature simulated annealing algorithm optimize the phase of the active RIS reflections. Joint optimization of base station (BS) beamforming and active RIS elements is achieved through alternating iterations to maximize the quality of the signal at the user’s end, while accounting for active RIS noise. Simulations verify the proposed scheme’s applicability to both continuous and discrete phase systems. Furthermore, it is demonstrated that 4-bit discrete-phase quantization is comparable to continuous-phase signal enhancement. •A hybrid continuous-discrete optimization algorithm for RIS phase shift design.•Temperature-adapted Simulated Annealing and maximum ratio transmission (MRT).•Optimizing active RIS reflection under power constraints to maximize system SNR.